On the role of sex steroids in biological functions by classical and non-classical pathways. An update - Pillerová, Miriam; Borbélyová, Veronika; Hodosy, Július; Riljak, Vladimír; Renczés, Emese; Frick, Karyn M; Tóthová, Ľubomíra (Frontiers in neuroendocrinology, 2021)
The sex steroid hormones (SSHs) play several roles in regulation of various processes in the cardiovascular, immune, muscular and neural systems. SSHs affect prenatal and postnatal development of various brain structures, including regions associated with important physiological, behavioral, cognitive, and emotional functions. This action can be mediated by either intracellular or transmembrane receptors. While the classical mechanisms of SSHs action are relatively well examined, the physiological importance of non-classical mechanism of SSHs action through membrane-associated and transmembrane receptors in the brain remains unclear. The most recent summary describing the role of SSHs in different body systems is lacking. Therefore, the aim of this review is to discuss classical and non-classical signaling pathways of testosterone and estradiol action via their receptors at functional, cellular, tissue level and to describe the effects on various body systems and behavior. Particular emphasis will be on brain regions including the hippocampus, hypothalamus, frontal cortex and cerebellum.
Keywords: těhotenství; Intracellular receptors; Gonadal Steroid Hormones; Gonadal hormones; Sex steroids; estrogeny; lidé; Testosterone; Classical/non-classical signaling; Estradiol; pohlavní steroidní hormony; Female; Hypothalamus; hypothalamus; Humans; estradiol; Transmembrane receptors; Brain structures; testosteron; Estrogens; Pregnancy; ženské pohlaví